Pembacaan Mubadalah terhadap Hadist Perempuan sebagai Aurat dan Implikasinya terhadap Relasi Gender - Haitomi, Faisal; Najwah, Nurun (Islamika Inside: Jurnal Keislaman dan Humaniora, 2020)
Abstract: This paper discusses the discourse on gender equality which is a hot issue to date. This research uses the mubadalah approach (annoyance/cooperation) which was initiated by Faqihuddin Abdul Kodir as an analysis tool. In the meantime, this research is focused on answering how the interpretation of mubad is from the hadith which is the object of this research. From the discussion presented, this research concluded that the editorial hadith about women as genitals which was later understood as the theological basis for housing women was not appropriate, because the main idea of ​​this hadith is not that of keeping the soul (Hifz Nafs), protecting the offspring (Hifz an-Nasl) and safeguarding property (Hifz al-Mal). Therefore, from the main idea of ​​the above hadith, it is concluded that it is not only women who are recommended to guard these three things, men on the other hand are also charged with the same responsibility.